Planning, Scheduling and Resource Allocation Analysis of a Court Project using Primavera P6 - Sumit Singh; Afzal Khan (International Journal of Scientific Research in Civil Engineering, 2022)
In this study, I am comparing a working project with a previously completed project of same aspect, for this research work we have chosen court project in vidisha. Which is on the verge of execution. For planning, scheduling and resource allocation we are using project management tool Primavera P6 8.3. From the study, it is found, how the project is planned, the sequence of work and linking relationships between activities for the whole project. In conclusion it is understood that, it is important to realize that there will be changes to the schedule logic as well as differences between the planned progress and actual progress. Based on the differences the schedule needs to be changed so as to complete the project smoothly.
Keywords: Primavera; Gantt Chart; Time-Cost Comparison; CPM Network; Tracking; Project Scheduling